State capitalism and performance persistence of business group-affiliated firms: A comparative study of China and India - Hu, Helen Wei; Cui, Lin; Aulakh, Preet S (Journal of International Business Studies, 2019)
Business groups emerged in developing economies through direct or indirect support from the state in order to overcome a variety of institutional voids and/or to further state objectives of economic growth. However, the efficacy of this organizational form and its associated governance structures have been debated given the dual possibility of business groups to allocate resources among its affiliates for cross-subsidization or winner-picking. We argue that elements of the institutional environment comprising of the state’s approach to organizations and the political context of these interactions vary across countries, thereby influencing business groups’ resource allocation strategies and affecting the persistence of affiliated firms’ superior performance. Contrasting the types of state capitalism in China and India, we develop and test our hypotheses. We find that the effect of business group affiliation on firms’ superior performance persistence is stronger in a state-led system of state capitalism (e.g., China) than in a co-governed system (e.g., India) and that this divergence of the business group effect is weakened as affiliated firms internationalize. Our findings have implications for understanding business groups across institutional contexts and the influence of diversity in the types of state capitalism on organizational strategies.